Price discrimination in many-to-many matching markets - Renato Gomes; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2011)
We study second-degree price discrimination in markets where the product traded by the monopolist is access to other agents. We derive necessary and sufficient conditions for the welfare and the profit-maximizing mechanisms to employ a single network or a menu of non-exclusive networks. We characterize the optimal matching schedules under a wide range of preferences, derive implications for prices, and deliver testable predictions relating the structure of the optimal pricing strategies to conditions on the distribution of match qualities. Our analysis sheds light on the distortions associated with the private provision of broadcasting, health insurance and job matching services.
Keywords: D82; 330; matching; two-sided markets; networks; adverse selection; incentives; mechanism design